Feasibility Analysis of Freshwater Fish Farming Business Development in Pringsewu District - Sirat, Muhiddin; Shaleh, Shofyan; Ermawati, Ratna; Sirat, Muhammad Mirandy Pratama; Utomo, Deny Sapto Chondro (AQUASAINS, 2020)
This research has two aims, the first was to see and analyze the business of freshwater fish farming in Pringsewu District which is feasible or not to be developed. The second aim was to find out whether the freshwater fish farming business in Pringsewu District remain feasible to be developed if there was a decrease in production levels and an increased in production costs. This research analyzes several aspects of business feasibility, namely marketing aspect, production aspect, management aspect dan financial aspect. In the financial aspect, two approaches were used, that were analysis of unpaid business feasibility using the Benefit Cost Ratio (B/C Ratio), Break event point (BEP), Return On Invesment (ROI) analysis tools and discounted business feasibility analysis with the Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C), Internal rate of retur (IRR), Gross Benefit Cost Ratio (Gross B/C), Payback period analysis tools. The results of this study indicate that the aspects of marketing, production aspect, and management aspect have the potential to be developed, as well as the financial aspects with the feasibility analysis of non-discounted shows that the business of freshwater fish farming in Pringsewu District is feasible to be developed. The results of the sensitivity analysis also show that the business is still feasible to be developed despite a decline in production levels and an increased in production costs.Â Keywords : Business Development, Business Feasibility, Project Evaluation, Freshwater Fish Farming